Altered diversity and composition of gut microbiota in patients with allergic rhinitis. (December 2021) - Zhou, Mu-shi; Zhang, Bin; Gao, Zhao-lin; Zheng, Ru-ping; Marcellin, Dama Faniriantsoa Henrio Marcellin; Saro, Adonira; Pan, Jing; Chu, Ling; Wang, Tian-sheng; Huang, Ju-fang
Abstract: Background: Recently, multiple studies have suggested an association between gut dysbiosis and allergic rhinitis (AR) development. However, the role of gut microbiota in AR development remains obscure. Methods: The goal of this study was to compare the gut microbiota composition and short-chain fatty acid (SCFAs) differences associated with AR (N = 18) and HCs (healthy controls, N = 17). Gut microbiota 16SrRNA gene sequences were analyzed based on next-generation sequencing. SCFAs in stool samples were analyzed by gas chromatography-mass spectrometry (GC-MS). Results: Compared with HCs, the gut microbiota composition of AR was significantly different in diversity and richness. At the phylum level, the abundance of Firmicutes in the AR group were significantly lower than those in the HCs group. At the genus level, the abundance of Blautia, Eubacterium_hallii_group, Romboutsia, Collinsella, Dorea, Subdoligranulum and Fusicatenibacter in the AR group were significantly lower than that in the HCs group. The concentrations of SCFAs were significantly lower in the AR group compared with the HCs group. Correlation analysis showed that the Eubacterium-hallii-group and Blautia correlated positively with SCFAs. Conclusion: Our results demonstrate compositional and functional alterations of the gut microbiome in AR. Highlights: GC-MS was utilized to identify and quantify intestinal microbial metabolites in adult AR. The Eubacterium-hallii-group and Blautia taxa associated favorably with SCFAs. Our investigation sheds light on changes in the gut microbiota and metabolite profiles in AR.